Pengaruh Preloading terhadap Kuat Geser Undrain - Syafruddin Syafruddin (Universitas Lambung Mangkurat, 2008)
Clay is kind of soil with fine grained that has low bearing capacity. Preloading cause change to water content and void ratio, result consolidation process. Consolidation on the clay cause big problem to the construction, that's why improvement characteristic of the clay is needed.The objective of this study is to know how much increasing undrain shear strength (Cu) to the clay consolidation degree as a part of effort to improvement the soil. In this experiment, Consolidation Test is preformed, the preloading to object test with consolidation degree at 10%, 20%, 30%, 40%, 50%, 70%, and 90%, and Unconfined Compression Test (UCT) as the last test on this experiment.The result of this study is a undrain shear strength equation (∆Cu)= -2.10-10U5-2.108U4+7.10-8U3+1.10-5U2+0,0015U-0,0008 for Penggalaman’s clay soil, as a reference to clay soil improvement.